Detection of Essential Oils of Patchouli Leaves (Pogostemon cablin Benth) with Combination of 2,4- Dichlorofenoxyacetate and Coconut Water In Vitro - Suci Rahayu (Talenta Publisher, 2021)
The study of essential oils detection of patchouli leaves (Pogostemon cablin Benth) with combination of 2,4-Dichlorofenoxyacetate and coconut water which produced calli had been done at Departement of Food Crops and Horticulture, Tissue Culture Laboratory, North Sumatra and the Organic Chemistry Laboratory of the Faculty of Mathematics and Natural Sciences, University of Sumatera Utara. The aim of the study was to determine the concentration of the combination of 2.4-D and coconut water which added in MS media for detection essential oils in patchouli calli in vitro. The experiment used factorial Completely Randomized Design (CRD) with two factors. The first factor was coconut water with concentrations of 0, 10 and 20%. The second factor is 2.4-D with a concentrations of 0, 0.5 and 1 ppm.The results showed that the optimum combination of 2,4-D and coconut water was capable to induce calli initiation after 13 DAP (days after planting), 80% of calli production, green color, nonfriable, and calli weight of 0,28 gram. The TLC (Thin Layer Chromatography) result showed that the treatment of 0.5 ppm 2,4-D and 10% coconut water produced the same Rf value as Rf standard (patchouli oil) which was 0.87